PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris pada SKPD di Kabupaten Blora - Irfan Ali Mustofa, 14.05.52.0160; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
The purpose of this research was to determine the influence of human resource competencies, the application of regional financial accounting systems, the application of government accounting standards and internal control systems to the quality of local government financial reports in the Blora District Regional Device work Units. This study uses a random sampling method in the selection of samples, with criteria that are Echelon III and IV Officials in the Office and Agency in Blora Regency chosen as respondents for the reason of seeing managerial performance in the Quality of Regional Financial Reports. The data used is primary data with the method used is a questionnaire method. Questionnaires were processed as many as 93 respondents. The data obtained will be analyzed using the instrument feasibility test, classic assumption test, multiple linear regression and research model test. Competence of human resources application of government accounting standards and internal control systems influence positive signigicant the quality of regional financial reports, and application of regional financial accounting systemss influence Negative signigicant the quality of regional financial reports Keywords : Competence of human resources, application of regional financial accounting systems, application of government accounting standards and internal control systems, quality of regional financial reports